Konstruksi Sosial Moderasi Beragama: Analisis Teori Konstruktivisme Berger dan Luckmann dalam Komunikasi Keagamaan Indonesia - Zainul Fanani; Nasirudin Al Ahsani (Fakultas Dakwah Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2025)
The issue of religious moderation in Indonesia is a critical concern amidst global challenges such as extremism and horizontal religious conflicts, as well as local dynamics like the influence of diverse religio-cultural norms. This study aims to analyze: (1) the social construction of religious moderation through Berger and Luckmann's theory, and (2) the role of religious communication in reinforcing moderation values. A library research method was employed, using qualitative analysis of selected literature (journals, books, policy documents) from credible databases. The findings reveal that religious moderation is constructed dialectically through externalization (values created), objectivation (values institutionalized), and internalization (values adopted by individuals), with religion as a dynamic social product. Religious communication—through education, digital media, and state policies—plays a strategic role in disseminating inclusive narratives, such as the Indonesian Ministry of Religious Affairs' programs integrating wasathiyyah (balance) into curricula and media content. Key findings emphasize that religious moderation is most effective when built through participatory interaction (not top-down) and contextual adaptation, supported by Indonesia's legal framework and multiculturalism. This study contributes to strengthening discourse on moderation based on social constructivism and transformative communication practices.